The Effect of Increased Glucose Induction on GSH Levels in Insulin Gaussia Luciferase (iGL) Cells Derived from Rat Pancreatic Beta Cells - Ardiansah, Fery; Stujanna, Endin Nokik; Sanjaya, Arief Indra; Listiyaningsih, Erlin; Ningsih, Sri Suciati; Ujianti, Irena; Lestari, Dwi Retna (Journal of Biomedicine and Translational Research, 2023)
Background: Prolonged hyperglycaemia can make the pancreatic beta cells work harder and cause fatigue. When this happens, it can trigger oxidative stress reactions, which can produce free radical compounds that can damage pancreatic beta cells. The body compensates by activating protective mechanisms such as the production of antioxidant compounds to reduce the levels of free radicals in the cells. One such compound is glutathione (GSH). Insulin Gaussia Luciferase (iGL) cells are a cell line derived from rat pancreatic β (beta) cells. These cells can be used as a model of oxidative stress in hyperglycaemia to measure GSH levels and there are no studies using iGL cells to measure GSH levels. Therefore, in this study, the iGL cells are used as the object of research.Objective: To investigate the effect of GSH levels on glucose toxicity condition through in vitro experiments on iGL cells.Methods: The study used 5 different glucose concentrations of 11, 16.5, 22, 33, and 44 mM with the addition of iGL cell growth medium exposed for 7 days. We measured the amount of intracellular GSH using a colourimetric method at a wavelength of 405 nm. The analysis used in this study was a one-way ANOVA test. Differences between groups were tested using SPSS.Results: The results of this study showed that there was an increasing trend in total GSH levels on the third and seventh day.Conclusion: there was a daily decrease in GSH/cell in the iGL sample cells exposed to different concentrations of glucose for 7 days. This can be due to an increase in the oxidative stress reactions in the cells, which can lead to a decrease in the levels of antioxidants.